Language : a complex-systems approach - Steyn, Jacques (Linguistics, 2016)
Mainstream twentieth-century linguistics, a segregational approach, cannot explain the most obvious characteristics of language. The reasons for this are investigated. It is concluded that linguistics suffers from an incoherent conceptual framework which is the result of influences from three major sources: 1. The desire to establish linguistics as a proper science which led to the acceptance of a mechanistic and positivistic view of science and a pre-quantum conception of matter. 2. The language myth: there are many notions about language and related issues which we have inherited from our ancestors and tacitly accepted without scrutiny. Contemporary ideas about language are biased by this inherited stock of 'knowledge'. 3. Saussure's theory of language, later adopted and adapted by Chomsky, in which the 'true object of linguistic investigation' is abstracted away from what we ordinarily view as language. Together these three sources resulted in a peculiar view of language which cannot explain the most obvious things about it. The proposed alternative view, an integrational approach, redefines language in the holistic terms of a complex-systems approach. Language is the outcome of the dynamic interaction between social and physiological systems -- particular attention is paid to consciousness. Neither language, society or culture is an 'object', but is created through the interaction between individuals in communicative situations. Language is not 'being', but results from 'becoming'. Meaning is not given in advance, but created in each event of communication. Meaning is not a static closed system, but an open system which is dynamically constructed from moment to moment. Concepts of mathematical topology (fractal geometry and catastrophe theory), non-linear, dynamic, open and complex systems, and of chaology are used as conceptual tools to break away from the stronghold our inherited view of language has on our contemporary thinking about it.